Rincón de lectura para la animación lectora de los niños y niñas de segundo año paralelo “A” de la Escuela De Educación Básica “García Moreno”, del Cantón Riobamba, Provincia de Chimborazo, año lectivo 2017-2018 - Zula Colcha, Cristina Elizabeth (2018)
The education of our country must provide activities where reading is encouraged, therefore institutions must have spaces that contain materials to stimulate reading from the first years; The purpose of this research was to determine the contribution of the reading corner in reading animation, since students are participants in an approach to reading. Through the proposed objectives, the fundamental aspects of the reading corner were established, and reading materials were identified according to age, which were: classic children's stories, illustrated books, and children's entertainment magazines. Strategies were made with these materials of reading animation to take advantage of the materials of the reading corner. We worked with a population of 32 students, which correspond to 18 children with an equivalent of 56.25 and 14 girls, corresponding to 43.75. This research was done with a qualitative approach and a descriptive methodology, for the verification of results, observation cards were used, where it can be concluded that the strategies motivate the students to use the reading corner. It is recommended that activities be varied so that students do not lose interest in reading.